Pengaruh Pengungkapan Enterprise Risk Management (ERM) Terhadap Nilai Perusahaan - Khalifah Syafitri; Dini Rosdini; Prima Yusi Sari (Jurnal Riset Akuntansi dan Keuangan, 2023)
The aim of this study was to determine the influence of enterprise risk management (ERM) disclosure on firm value. The sample in this study were companies listed on the Indonesia Stock Exchange (IDX) in 2017-2019, as many as 81 companies were obtained using the purposive sampling method. The analytical technique used is linear regression analysis. The results of the study indicate that ERM disclosure has an effect on firm value.